Clarifying some issues on the geoeffectiveness of limb halo CMEs - Cid, C. (2013)
A recent study by Cid et al. (2012) showed that full halo coronal mass ejections (CMEs) coming from the limb can disturb the terrestrial environment. Although this result seems to rise some controversies with the well established theories, the fact is that the study encourages the scientific community to perform careful multidisciplinary analysis along the Sunto- Earth chain to fully understand which are the solar triggers of terrestrial disturbances. This paper aims to clarify some of the polemical issues arisen by that paper. © 2013 International Astronomical Union.